Staff Studies for the World Economic Outlook, 1997. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
These studies provide supporting material for the analysis and scenarios in the World Economic Outlook.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet